2012
DOI: 10.4103/0970-0218.94013
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication patterns and drug use behavior in housewives belonging to the middle income group in a city in northern India

Abstract: Objectives:The objective was to assess the self-medication patterns and drug use behavior in housewives belonging to the middle income group in a city of Haryana State in Northern India.Materials and Methods:A detailed questionnaire designed to assess the self-medication patterns and drug use behavior and interview technique was used to elicit the requisite information. One hundred housewives of the middle income group were interviewed in Rohtak.Results:Most of the housewives were in the habit of keeping the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
42
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 6 publications
7
42
2
2
Order By: Relevance
“…12,14 In contrast to this finding Stephen et al (59.5%), Chari et al (51.4%) and Kaushal et al (49.0%) stated that previous doctor's prescription were the most common sources of self medication. 10,11,15 Maximum study subjects (45%) stated that they practice self medication because of high consultation fee of doctors which was the same observation by Kulkarni et al, Adhikary et al and Shankar et al 7,8,12 A study conducted in rural Maharashtra by Phalke VD et al found that the major reason for self medication were economic (58.5%) and non availability of health care facility (29.3%). 16 Other common reasons for self medication were why to consult doctors for minor illness, lack of time, easy availability of OTC drugs etc.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…12,14 In contrast to this finding Stephen et al (59.5%), Chari et al (51.4%) and Kaushal et al (49.0%) stated that previous doctor's prescription were the most common sources of self medication. 10,11,15 Maximum study subjects (45%) stated that they practice self medication because of high consultation fee of doctors which was the same observation by Kulkarni et al, Adhikary et al and Shankar et al 7,8,12 A study conducted in rural Maharashtra by Phalke VD et al found that the major reason for self medication were economic (58.5%) and non availability of health care facility (29.3%). 16 Other common reasons for self medication were why to consult doctors for minor illness, lack of time, easy availability of OTC drugs etc.…”
Section: Discussionmentioning
confidence: 52%
“…were commonly used for self medication. 4,9,10,12,14 Loharkar et al and Stephen et al found that even sedative drugs were used for self medication which comes under schedule H and cannot be purchased over the counter without the prescription of a qualified doctor. 11,13 We observed pharmacists (48.7%) as the most common source of information about OTC drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A study done in a city of Northern India, most of the housewives were in the habit of keeping the medicines though only 73% of them were in the habit of using it without any prescription. 16 In New Delhi, study done by Lal, the prevalence of selfmedication among those who had suffered some illness episode in the last one month was 31.3%. 17 A study done by Arun et al, the prevalence of self-medication was 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Brand was selected on the basis of previous experience (48.8%) while in 21.3% cases it was suggested by pharmacist & chemist. Only 62% of participants knew that SM can be harmful 5 .…”
mentioning
confidence: 99%